Detection of microvascular complications of diabetes by EZSCAN method and their correlation with metabolic indices - Tiwari, Alankar; Pandey, Saumya (International Journal of Research in Medical Sciences, 2019)
Background: EZSCAN is a new, non-invasive technique to detect sudomotor dysfunction and thus neuropathy in diabetes patients at an early stage. It further predicts chances of development of other microvascular complications. In this study we evaluated EZSCAN for detection of microvascular complications in Type 2 diabetes patients and assessed their correlation with various metabolic parameters. Methods: 104 known diabetes patients, 56 males and 48 females, were studied. All cases underwent the EZSCAN test, Body mass index measurement, fasting and postprandial blood glucose, HbA1c tests. Diabetes related complications were thereafter correlated with various metabolic indices. Results: Strong correlation was found between HbA1c, body mass index (BMI), fasting blood glucose (FBG) and post-prandial blood glucose (PPBG) with diabetes related microvascular complications assessed by EZSCAN, strongest being with FBG (r=0.755) and weakest with BMI(r=0.232). Conclusions: Microvascular complications of diabetes as detected by EZSCAN method correlate strongly with metbolic indices of the patient and thus EZSCAN can be used as a simple, non-invasive and quick method to detect microvascular complications of diabetes.